2010
DOI: 10.1021/cb1000422
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a Small Molecule at a Protein–Protein Interface Regulates the Chaperone Activity of Hsp70–Hsp40

Abstract: Heat shock protein 70 (Hsp70) is a highly conserved molecular chaperone that plays multiple roles in protein homeostasis. In these various tasks, the activity of Hsp70 is shaped by interactions with co-chaperones, such as Hsp40. The Hsp40 family of co-chaperones binds to Hsp70 through a conserved J-domain, and these factors stimulate ATPase and protein-folding activity. Using chemical screens, we identified a compound, 115-7c, which acts as an artificial co-chaperone for Hsp70. Specifically, the activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
168
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(179 citation statements)
references
References 62 publications
10
168
0
Order By: Relevance
“…We used the tool compound MAL3-101 (20) to assess whether HSP70 chaperone function is required for survival in a panel of patient-derived, fusion-driven solid cancer models (Table S1). MAL3-101 is a specific HSP70 inhibitor that binds to an allosteric site within the chaperone's ATPase domain, thus inhibiting catalytic activation by J domain-containing HSP40 chaperones (21). We found that different fusion-driven cancer models were not uniformly sensitive to inhibition of HSP70 activity but rather that RMS cell lines exhibited a unique MAL3-101 sensitivity (Fig.…”
Section: Hsp70 Functionmentioning
confidence: 82%
“…We used the tool compound MAL3-101 (20) to assess whether HSP70 chaperone function is required for survival in a panel of patient-derived, fusion-driven solid cancer models (Table S1). MAL3-101 is a specific HSP70 inhibitor that binds to an allosteric site within the chaperone's ATPase domain, thus inhibiting catalytic activation by J domain-containing HSP40 chaperones (21). We found that different fusion-driven cancer models were not uniformly sensitive to inhibition of HSP70 activity but rather that RMS cell lines exhibited a unique MAL3-101 sensitivity (Fig.…”
Section: Hsp70 Functionmentioning
confidence: 82%
“…This profile is shared with other allosteric Hsp70 inhibitors. 17,18,34,36,37 As another test of chaperone function, we measured the effects of the compounds on the binding of Hsp70 to a misfolded protein. In previous work, MKT-077 stabilized the interaction between prokaryotic Hsp70 (DnaK) and denatured luciferase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8,15,16 In fact, only a handful of known Hsp70 inhibitors, including 115-7c 17,18 and MKT-077, 19,20 are Hsp70-selective in cells and none of these compounds are known to pass the blood-brain barrier (BBB). Accordingly, the major objective of this study was to generate an analogue that might be suitable for use in the CNS.…”
mentioning
confidence: 99%
“…Following on this work, we recently found that one promising example of this chemical class, 115-7c, stimulates ATP turnover by directly favoring interactions between Hsp70s and J proteins (Fig. 1A) (36,37). Moreover, 115-7c is membrane permeable, selective for Hsp70 and does not induce a stress response (36), so it can be used to selectively tune Hsp70 activity in cells without impacting chaperone expression.…”
mentioning
confidence: 86%